2022
DOI: 10.30574/gscbps.2022.18.3.0115
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological assessment of borehole water in some communities in Owerri West, Southeastern Nigeria

Abstract: The proliferation of boreholes dug by individuals, public and private entities in a bid to overcome the problem of water shortage has caused various communities in Owerri West, southeastern Nigeria to depend on borehole water as readily available water for drinking and domestic purposes. Unfortunately, the water is not treated before it is used for drinking and there is no surveillance of bacteria in the water to ascertain its safety. In consideration of this fact, a study was conducted to assess the bacteriol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…with a high MDR can pose a threat of being a secondary pathogen of health importance (Shar et al, 2010). The report of Ewelike et al (2022) suggested that the microbes obtained from the portable water sources in Owerri municipal had similar organisms as observed in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…with a high MDR can pose a threat of being a secondary pathogen of health importance (Shar et al, 2010). The report of Ewelike et al (2022) suggested that the microbes obtained from the portable water sources in Owerri municipal had similar organisms as observed in the present study.…”
Section: Discussionsupporting
confidence: 79%